2018
DOI: 10.1111/sltb.12533
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Inflexibility Predicts Suicidality Over Time in College Students

Abstract: Objective It is essential to identify modifiable risk factors that can be targeted to reduce suicidal ideation (SI) and behavior in college students. Psychological inflexibility, a pattern of responding to internal experiences in a literal and rigid way, and attempting to control those experiences even when it interferes with valued living, could theoretically lead to SI or increase its intensity. Method Psychological inflexibility and its component processes were tested as a predictor of SI in a longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In line with ACT’s transdiagnostic model of psychopathology ( 26 ), one potential explanation for the impact of psychedelics on depression severity and suicidality is via decreases in experiential avoidance. Experiential avoidance is prospectively predictive of depression severity [e.g., ( 69 , 70 )] and suicidal ideation [e.g., ( 71 , 72 )]. Moreover, within psychotherapeutic treatments, decreases in experiential avoidance are associated with, and predictive of, subsequent decreases in depression severity ( 73 , 74 ) and suicidal ideation ( 74 , 75 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with ACT’s transdiagnostic model of psychopathology ( 26 ), one potential explanation for the impact of psychedelics on depression severity and suicidality is via decreases in experiential avoidance. Experiential avoidance is prospectively predictive of depression severity [e.g., ( 69 , 70 )] and suicidal ideation [e.g., ( 71 , 72 )]. Moreover, within psychotherapeutic treatments, decreases in experiential avoidance are associated with, and predictive of, subsequent decreases in depression severity ( 73 , 74 ) and suicidal ideation ( 74 , 75 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ellis and Rufino (2016) found that increased experiential avoidance was associated with an increase in suicidal ideation in hospitalized psychiatric patients after controlling for depression and hopelessness. Recently, Krafft, Hicks, Mack, and Levin (2019) have shown -in a sample of young adults -that experiential avoidance is a robust pre-This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%
“…The negative correlation with the coping strategy of problem-solving can also be expected, as psychological rigidity can be viewed as a deteriorating factor for shifting between different strategies and persisting in problem-solving (Kashdan et al, 2006;Kashdan & Rottenberg, PSIHOLOGIJA, 2020, Vol. 53(2), 161-181 2010; Krafft, Hicks, Mack, & Levin, 2018). On the other hand, as the AAQ-II is aimed at assessing the inner processes of a person dealing with private emotional experiences, it happens to be unrelated to communicating these experiences in a social context operationalized by the coping strategy of seeking social support, defined as actively turning to others for comfort, help, and advice (Amirkhan, 1990), as well as by concealing emotional regulation, defined as a social skill of hiding emotional experiences and withholding expression in the presence of others (Hofmann & Kashdan, 2010).…”
Section: Discussionmentioning
confidence: 99%